2012
DOI: 10.4102/satnt.v31i1.368
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous knowledge in the life sciences classroom: Science, pseudo-science or a missing link?

Abstract: Die redaksionele span van die Suid-Afrikaanse Tydskrif vir Natuurwetenskap en Tegnologie erken hiermee die waardevolle, belangrike rol wat eweknie-evalueerders tydens die algehele publikasiesproses vervul -nie alleen in die vorming van individuele manuskripte nie, maar ook in die vestiging van die kredietwaardigheid en aansien van ons joernaal. Ons is daartoe verbind om alle oorspronklike, innoverende bydraes, wat vir publikasie voorgelê word, tydig te publiseer. Daarom is die identifisering en keuse van kundi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Thabo Mbeki (1998) expressed the following viewpoint in his African renaissance speech of 1998: Perhaps, the new generation of scientists will find inspiration in the country's rich IK, to solve problems like the HIV and AIDS pandemic and the high unemployment, to mention but two problems that the country grapples with. Mothwa (2014) have shown that there are many teachers who have objections to teaching IK. One reason for this opposition is teachers' negative perceptions of IK, which are often fuelled by naïve understandings of the tenets of both IK and science.…”
Section: Addressing the 'Missing Link' In Stem Education: The Affective Domainmentioning
confidence: 99%
See 2 more Smart Citations
“…Thabo Mbeki (1998) expressed the following viewpoint in his African renaissance speech of 1998: Perhaps, the new generation of scientists will find inspiration in the country's rich IK, to solve problems like the HIV and AIDS pandemic and the high unemployment, to mention but two problems that the country grapples with. Mothwa (2014) have shown that there are many teachers who have objections to teaching IK. One reason for this opposition is teachers' negative perceptions of IK, which are often fuelled by naïve understandings of the tenets of both IK and science.…”
Section: Addressing the 'Missing Link' In Stem Education: The Affective Domainmentioning
confidence: 99%
“…The above also poses a problem for teachers. In a culturally diverse classroom, whose IK should be taught (De Beer & Mothwa 2014)? Also, teachers do not have sufficient knowledge of all these different IKS.…”
Section: Implications For Pre-and In-service Teacher Educationmentioning
confidence: 99%
See 1 more Smart Citation